Do Online Customer Reviews Matter? A Study of Woman's Buying Interest in Beauty Products - Keisha Safina Syauta; Daniel Hermawan (Universitas Muhammadiyah Yogyakarta, 2023)
The growth of internet users in Indonesia is accelerating rapidly, especially in 2022. This surge in internet users can be attributed to the pandemic's impact on lifestyle, which encourages people to adopt digital products, including reliance on online customer reviews for product information. This study aims to determine the influence of online customer reviews on buying interest in beauty products. Researchers used quantitative methods and non-probability techniques with purposive sampling using an online questionnaire with the criteria of customers (women) who use and have read beauty product reviews. Researchers obtained 122 respondents who were analyzed using multiple linear regression analysis techniques. The results proved that online customer reviews covering all dimensions influenced purchase intention. The credibility of a review and reviewers as in the dimension of review credibility is important for customers reading online customer reviews to influence buying interest in beauty products. This research helps beauty product owners to understand and utilize online customer reviews in their business.